2019
DOI: 10.3168/jds.2018-15400
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of flavored concentrate premixes by young ruminants following a short-term exposure

Abstract: Three cafeteria feeding design experiments were conducted to test whether young ruminants have flavor preferences. Experiment 1 was with 11 Dorset × Suffolk weaned lambs of both sexes, aged 5 mo and averaging 47.5 (standard deviation = 5.8) kg of body weight. The lambs were offered a choice of 5 flavored concentrate premixes (FCP) and an unflavored control for 5 min 4 times over 10 d. The FCP were prepared by mixing 200 to 300 g/t (as-is basis) of synthetic flavors (vanilla, milky, spicy/fenugreek, red summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The lack of preference for nexulin was in agreement with the findings of Oh et al [ 32 ], who reported a sharp decrease in DMI after supplementing cows’ total mixed ration with nexulin. In this study, consumption of the flavoured grain mixture did not increase relative to control, in agreement with studies carried out in cows [ 11 ] and lambs [ 30 ]. Calves with good appetite (above 600 g/d) also showed a lack of preference when fed an orange or unflavoured starter ration, while those with a low appetite (below 600 g/d) preferred an orange flavoured ration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lack of preference for nexulin was in agreement with the findings of Oh et al [ 32 ], who reported a sharp decrease in DMI after supplementing cows’ total mixed ration with nexulin. In this study, consumption of the flavoured grain mixture did not increase relative to control, in agreement with studies carried out in cows [ 11 ] and lambs [ 30 ]. Calves with good appetite (above 600 g/d) also showed a lack of preference when fed an orange or unflavoured starter ration, while those with a low appetite (below 600 g/d) preferred an orange flavoured ration.…”
Section: Discussionsupporting
confidence: 93%
“…These findings contrast with our findings where orange was the least preferred flavour among the liquid aroma flavours, and juicy orange flavour did not differ in preference among the powder-aroma flavours offered. Lambs preferred milky over fenugreek in this study, in agreement with the findings of Nedelkov et al [ 30 ], but the preference for anise over fenugreek was contrary to the findings of Harper et al [ 11 ], where cows were found to prefer fenugreek over anise. The discrepancies between studies may be due to the animal species used or the flavour inclusion rate.…”
Section: Discussionsupporting
confidence: 91%
“…In ruminants, the variation of only one of the sensory characteristics of the diet is enough to change the feed intake of the animals ( 25 ). Systematic studies investigate the taste preference of ruminants, aiming to provide information on the acceptance of synthetic blends and flavors ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the effects of feed sensory attributes on dietary preference in ruminants [4][5][6]. Volatile organic compounds have often been screened for their effect on preference of forages, and many had associations with preference.…”
Section: Introductionmentioning
confidence: 99%
“…Un-inoculated pellets stored at ambient temperatures (CA) or 5 • C (CB) and H57 inoculated pellets stored at ambient temperatures (HA) or 5 • C (HB) 3. Microbial volatile organic compounds (mVOCs) were identified by details given at http://bioinformatics.charite.de/mvoc/index.php?site=home 4. The contrast between the means 5.…”
mentioning
confidence: 99%